Determining The Influence Of Current Ratio, Return On Assets, Total Assets Turnover Ratio And Debt To Equity Ratio On Stock Return (A Study Of The Manufacturing Company Listed In Indonesia Stock Exchange Period 2010-2014) - Chrislie Angelia Lie; Partogian Sormin (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2016)
The objective of this research is to analyze the influence of Current Ratio (CR), Return on Assets (ROA), Total Assets Turnover (TATO), and Debt to Equity Ratio (DER) towards the Stock Return (SR) for the companies listed in Indonesian Stock Exchange over period 2010-2014. Sample of this research is 51 (fifty one) manufacturing companies that listed in Indonesia Stock Exchange for the period 2010-2014 totaling the sample of 255 (two hundred fifty five) sample in this research. The analysis technique is using the multiple linear regression and hypotheses testing using t-test to examine partial regression and F-test to examine the simultaneous regression using program Stata 13.0 with significance level of 95%. The research results that Return on Assets (ROA) turns out to be significant and positively affecting the Stock Return (SR). The Current Ratio is not significant and negatively affects the Stock Return (SR). Total Assets Turnover (TATO) and Debt to Equity Ratio (DER) is not significant and positively affect the Stock Return (SR). In this case, Return on Assets would be the best consideration for investor who wants to invest their money.Keywords: Stock Return, Current Ratio, Total Assets Turnover Ratio, Debt to Equity Ratio.